High pressure behavior of P2O5 crystalline modifications: compressibility, elastic properties and phase transitions. (5th February 2015) - Brazhkin, V V; Gromnitskaya, E L; Danilov, I V; Katayama, Y; Lyapin, A G; Popova, S V
Abstract: Solid phases of the P2 O5 compound have rarely been studied under high pressure to date due to their record-high hygroscopicity. We present the results of in situ x-ray diffraction study of the structure of P2 O5 molecular and polymeric modifications under pressures up to 11 GPa, as well as the results of an ultrasonic study of a molecular phase up to 2 GPa. At low pressures (0.3–0.7 GPa), there is a structural transformation in the molecular phase accompanied by a significant (7–8%) density increase. This phase transition is accompanied by a large increase of both the shear modulus (by 30–40%) and bulk modulus (by 20–25%). Compression curves of the molecular and polymeric covalent phases asymptotically converge to each other at 9–10 GPa and reach a density of 3.6–3.7 g cm −3 . The polymeric modification is 'typical' for covalent oxides values of the bulk modulus and its derivative: B ≈ 35–40 GPa, B′P  ≈ 3–4. The molecular phase has quite small values of the bulk and shear moduli (B ≈ 12 GPa, G ≈ 5 GPa).